Construction of the waaF Subunit and DNA Vaccine Against Escherichia coli in Cow Mastitis and Preliminary Study on Their Immunogenicity - Wang, Hua; Yuan, Ligang; Wang, Tao; Cao, Lu; Liu, Fukang; Song, Juanjuan; Zhang, Yong (Frontiers in Veterinary Science, 2022)
Escherichia coli (E. coli) is one of the major pathogenic bacteria in bovine mastitis, which usually triggers systemic symptoms by releasing lipopolysaccharide (LPS). waaF is the core in LPS pathogenicity. In this study, a new waaF vaccine candidate was identified, constructed with the pcDNA3.1 (+)HisB-waaF plasmid to create to a DNA vaccine (pcwaaF), and transfected into MCF-7 cells to produce recombinant waaF subunit vaccine (rwaaF). After that, the safety of the two vaccine candidates was evaluated in mouse model. Immunogenicity and mortality of challenged mice were compared in 20 and 40 μg per dose, respectively. The results showed that rwaaF and pcwaaF were successfully constructed and the complete blood count and serum biochemical indicated that both of the vaccine candidates were safe (p > 0.05). In addition, histopathological staining showed no obvious pathological changes. The immune response induced by rwaaF was significantly higher than that of pcwaaF (p < 0.01), indicated by levels of serum concentration of IgG IL-2, IL-4, and IFN-γ, and feces concentration of sIgA. Survival rates of mice in rwaaF groups (both 80%) were also higher than in the pcwaaF groups (40 and 50%, respectively). Comparing the safety, immunogenicity, and E. coli challenge of two vaccine candidates, rwaaF had the better effect and 20 μg rwaaF was more economical. In conclusion, this study demonstrates the utility of a new E. coli vaccine and provides a rationale for further investigation of bovine mastitis therapy and management.